(untitled) (Economic studies journal, 2022)
This study aims to identify the viewpoint of the students of the Faculty of Commerce at Al-Zaytoonah University about the economic benefit of Facebook in e-marketing, since communication sites have a special place in the lives of young people daily, and they can be used as a final consumer or a commercial consumer (seller). This study has been divided into three sections, and the human limits of the study are students of the Faculty of Commerce, Al-Zaytoonah University. The time limits extend from 2020 to 2021. Concerning the spatial limits, the study includes students randomly selected from the Faculty of Commerce, Al-Zaytoonah University in Tarhuna City, Libya. The electronic questionnaire has been designed on Google Forms: Https://forms.gle/HbLwAoNaY3ri19BM and in study groups of students, and (83) responses have been obtained from the study community. The questionnaire, which is translated into information, shows that the volume of trade exchange (selling and buying) is still weak and faces several obstacles. The study also shows that most of the sample members, 72.3% of the study sample, have not made any sales process on social media platforms. At the purchasing level, 41% of the study sample does not make any purchase due to several reasons mentioned in the results of this study at the end of Chapter Three, the practical framework.